Clinical researchPrevalence of cigarette smoking and smoking-related disease correlates in Iranian asymptomatic HBV carriers - Alavian, Seyed M; Zarchi, Ali A.K; Javadipour, Morteza; Assari, Shervin; Keshvari, Maryam; Behnava, Bita (Archives of Medical Science, 2007)
HBV, asymptomatic carriers, cigarette smoking.